Proceso de ASC - OPTIMIZACION DEL PROCESO DE FABRICACION, PRODUCCION Y RECICLADO DE LA ARCILLA INDUSTRIAL DE PROTOTIPADO CLAY-FASE 2 (2021)
“Industrial or prototyping clays” (Industrial Clay) are materials malleable and moldable to make three-dimensional models; and offer great versatility; since they can be worked either manually (sculpted) or digital (CNC routed); and due to their properties it is possible to use and reuse them again, without having to waste material or discard already made models during the process. The present project; For its part, it aims to standardize a production and recycling process of this material and take it to a larger scale in order to allow a much higher production and recycling volume. Through workflows and methods to industrialize and optimize processes. All the above with the purpose of increasing the capacity and quality of the current production and recycling of clay. Thus allowing you to reach great scales.